The Change of Job Opportunities: the Role of Computerization and Institutions - Viki Nellas; Elisabetta Olivieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
This paper studies the pattern of job opportunities over the last two decades in European countries. We find that the share of high-skilled jobs have been expanding over time, while the share of medium-skilled jobs have been declining. These changes are in line with the US patterns and, according to the previous literature, they come from recent technological changes. However, our data show an interesting difference between the US and Europe: in Europe there is not any increase in the share of low-skilled employment. Moreover, we find that the difference between the proportion of employment hired in low-skilled and medium-skilled jobs is negatively correlated with both the unemployment rate and the degree of employment protection in the labour market. We propose a theoretical model to study the effects of a technological shock on the employment structure in a unionized economy. By accounting for the collective bargaining process, our model may fit Continental Europe better than the previous ones. We conclude that the definition of the union policy is crucial in order to explain observed cross-country heterogeneity in low-skilled employment.
Keywords: J2; J51; O3; 330